Materials to the Polish flora in the Herbarium of the University of Łódź. Part XX - the genus Potentilla L. (rosaceae) - Kołodziejek, Jeremi (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2008)
The study contains the revision of the herbarium specimens of the genus Potentilla (Rosaceae) preserved in Herbarium Universitatis Lodziensis - Department of Botany (LOD). The list of species consists of 28 taxa of Potentilla found on 605 localities althogether.